Multienzyme nanoassemblies: from rational design to biomedical applications. (14th October 2021) - Li, Di; Xiong, Qirong; Liang, Li; Duan, Hongwei
Abstract : This review summarizes the state-of-art strategies to prepare multienzyme nanoassemblies (MENAs), rational design of MENAs and their biomedical applications. Abstract : Multienzyme nanoassemblies (MENAs) that combine the functions of several enzymes into one entity have attracted widespread research interest due to their improved enzymatic performance and great potential for multiple applications. Considerable progress has been made to design and fabricate MENAs in recent years. This review begins with an introduction of the up-to-date strategies in designing MENAs, mainly including substrate channeling, compartmentalization and control of enzyme stoichiometry. The desirable properties that endow MENAs with important applications are also discussed in detail. Then, the recent advances in utilizing MENAs in the biomedical field are reviewed, with a particular focus on biosensing, tumor therapy, antioxidant and drug delivery. Finally, the challenges and perspectives for development of versatile MENAs are summarized.